Phylogenetic analysis of Dengue virus and insect-specific Flavivirus in Aedes aegypti from Gresik, Indonesia 2019 - RASYID NOOR HAKIM; MAMIK DAMAYANTI; SHIFA FAUZIYAH; TEGUH HARI SUCIPTO (Society for Indonesian Biodiversity, 2024)
Abstract. Hakim RN, Damayanti M, Fauziyah S, Sucipto TH. 2024. Phylogenetic analysis of Dengue virus and insect-specific Flavivirus in Aedes aegypti from Gresik, Indonesia 2019. Biodiversitas 25: 2340-2347. The spread of several Flaviviruses, such as Dengue virus and insect-specific Flavivirus, is periodically detected in Indonesia, including Surabaya, which is an endemic area. Gresik, as one of Surabaya's satellite cities, has high traffic mobility between regions, increasing the possibility of viral transmission. In this study, we identified Flaviviruses from Aedes aegypti mosquito isolates from Gresik collected in 2019. We also revealed the possibility of virus transmission from Surabaya to Gresik. The mosquito samples were collected using mosquito trap method. The Flavivirus Partial Nonstructural Protein 5 (NS5) -encoding gene region was isolated via the nested reverse transcription-polymerase chain reaction method. Sequence alignment and phylogenetic analysis were carried out to determine the kinship of Gresik strain virus isolates with the GenBank database. The results revealed that six out of 29 isolated samples (Sample from Duduk Sampeyan (47 and 43), Mengare (212 and 31), Kedamean (58), and Manyar (38)) exhibited a 220 bp DNA band, which corresponds to the NS5 gene. Further analysis using basic local alignment search tool - nucleotide and phylogenetic methods revealed that two sample sequences (38 and 212) are closely related to DENV-1 genotype 1, while the other four (31, 43, 47, and 58) are associated with Insect-Spesific Flavivirus (ISF). The similarity in NS5 partial sequence and genotype classifications of the dengue virus suggests the potential transmission of the virus from Surabaya to Gresik. We hypothesize that this phenomenon is closely linked to the population mobility between the two areas.